2003
DOI: 10.1063/1.1606103
|View full text |Cite
|
Sign up to set email alerts
|

Birefringence of GaN/AlGaN optical waveguides

Abstract: Phase-matched optical second-harmonic generation in GaN and AlN slab waveguides

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…III-nitride based waveguides (WGs) have indeed great potential in this spectral range not only because of the material transparency but also because of the low-temperature sensitivity of their index of refraction, which is one order of magnitude smaller than that of InP. Hui et al have demonstrated WG-based 2 2 directional couplers as well as 1 8 arrayed-WG gratings at m [3], [4]. Thanks to the large conduction band offset of up to 1.75 eV offered by nitride heterostructures, these materials also offer prospects for active optoelectronic devices at telecommunication wavelengths relying on intersubband (ISB) transitions Manuscript received July 10, 2007;revised September 7, 2007.…”
Section: Introductionmentioning
confidence: 99%
“…III-nitride based waveguides (WGs) have indeed great potential in this spectral range not only because of the material transparency but also because of the low-temperature sensitivity of their index of refraction, which is one order of magnitude smaller than that of InP. Hui et al have demonstrated WG-based 2 2 directional couplers as well as 1 8 arrayed-WG gratings at m [3], [4]. Thanks to the large conduction band offset of up to 1.75 eV offered by nitride heterostructures, these materials also offer prospects for active optoelectronic devices at telecommunication wavelengths relying on intersubband (ISB) transitions Manuscript received July 10, 2007;revised September 7, 2007.…”
Section: Introductionmentioning
confidence: 99%
“…The birefringence of DFT-calculated GaN aligns well with previously reported experimental values where a value of Δn ~0.0425 by Pezzagna and co-workers was obtained, whereas Sanford and co-workers reported Δn ~0.038 47 , 55 . Hui and co-workers reported Δn ~0.04 and Shokhovets and co-workers have reported a varying birefringence, that increases with increasing photon energy and ranges between 0.037 and 0.056 46 , 56 . In this work, we obtained a birefringence for GaN that increases slowly from 0.044 to 0.051 for energies approaching the band edge.…”
Section: Methodsmentioning
confidence: 99%
“…7 the birefringence of dilute-P GaNP alloys as a function of photon energy is presented, where the P-content is varied from 0% up to 12.5%. Previously reported values for GaN by Hui and co-workers have shown a birefringence of Δn ~ 0.04, while Pezzagna and co-workers measured a value of Δn ~ 0.0425 67,77 . Moreover, Shokhovets and co-workers have shown that the birefringence is an increasing function for photon energies up to the band gap of GaN and that it varies between 0.037–0.056 68 .…”
Section: Introductionmentioning
confidence: 91%